PELAKSANAAN TUGAS POKOK APARATUR DI BAGIAN ORGANISASI SEKRETARIAT DAERAH KABUPATEN KETAPANG - Santi Rahmawati E.42009024 (FISIP Universitas Tanjungpura Pontianak, 2013)
This Skripsi has purpose to analyze execution main task local aparatus based on ideal prespective bureaucracy especially coordination in Organization Office Local Secretariat Ketapang County Thetitle of skripsi based on problems concerning coordination internly and externly which didn’t apply byapparatus. Though both of them has been known and been guidance for goverment organization toexecute main task. However, applied coordination principles around West Borneo area didn’t execute itdecently yet. This research is description research has type exploration with qualitative method.Collection of data by interview technique, observation, and documentation study. Research subjects areOrganization Office Aparatus and the others apparatus who had choosen purposively. Conclusion ofthis research is lack of attempt that is applied by Organization Office to execute coordination decently.Briefly, such a goverment organization execute main task that should alteration interconnected the wayto do coordination externly. Keyword : Organization Office, Main Task,Coordination dan Aparatus.